Barriers to effective treatment of pediatric solid tumors in middle‐income countries: Can we make sense of the spectrum of nonbiologic factors that influence outcomes?. Issue 1 (16th October 2013) - Friedrich, Paola; Ortiz, Roberta; Fuentes, Soad; Gamboa, Yéssica; Ah Chu‐Sanchez, María Sabina; Arambú, Ingrid Carolina; Montero, Margarita; Báez, Fulgencio; Rodríguez‐Galindo, Carlos; Antillón‐Klussmann, Federico; ,
Abstract : BACKGROUND: The delivery of effective treatment for pediatric solid tumors poses a particular challenge to centers in middle‐income countries (MICs) that already are vigorously addressing pediatric cancer. The objective of this study was to improve the current understanding of barriers to effective treatment of pediatric solid tumors in MICs. METHODS: An ecologic model centered on pediatric sarcoma and expanded to country as the environment was used as a benchmark for studying the delivery of solid tumor care in MICs. Data on resources were gathered from 7 centers that were members of the Central American Association of Pediatric Hematologists and Oncologists (AHOPCA) using an infrastructure assessment tool. Pediatric sarcoma outcomes data were available, were retrieved from hospital‐based cancer registries for 6 of the 7 centers, and were analyzed by country. Patients who were diagnosed from January 1, 2000 to December 31, 2009 with osteosarcoma, Ewing sarcoma, rhabdomyosarcoma, and other soft tissue sarcomas were included in the analysis. To explore correlations between resources and outcomes, a pilot performance index was created. RESULTS: The analyses identified specific deficits in human resources, communication, quality, and infrastructure. The treatment abandonment rate, the proportion of metastatic disease at diagnosis, the relapse rate, and the 4‐year abandonment‐sensitive overall survival (AOS) rate varied considerably by country, ranging from 1% to 38%, from 15% to 54%, from 24% to 52%, and from 21% to 51%, respectively. The treatment abandonment rate correlated inversely with health economic expenditure per capita ( r  = −0.86; P  = .03) and life expectancy at birth ( r  = −0.93; P  = .007). The 4‐year AOS rate correlated inversely with the mortality rate among children aged <5 years ( r  = −0.80; P  = 0.05) and correlated directly with the pilot performance index ( r  = 0.98; P  = 0.005). CONCLUSIONS: Initiatives to improve the effectiveness of treatment for pediatric solid tumors in MICs are warranted, particularly for pediatric sarcomas. Building capacity and infrastructure, improving supportive care and communication, and fostering comprehensive, multidisciplinary teams are identified as keystones in Central America. A measure that meaningfully describes performance in delivering pediatric cancer care is feasible and needed to advance comparative, prospective analysis of pediatric cancer care and to define resource clusters internationally. Cancer 2014;120:112–125 . © 2013 American Cancer Society . Abstract : Effective delivery of pediatric solid tumor care poses a challenge to centers in low‐income and middle‐income countries. However, the complex variety of factors involved in delivery of care can be conceptualized in discrete components, analyzed using transparent methods, and interpreted in ways meaningful to leadership at a pediatric cancer center.